2016
DOI: 10.1111/apa.13445
|View full text |Cite
|
Sign up to set email alerts
|

The presence of physician champions improved Kangaroo Mother Care in rural western India

Abstract: Aim This study determined the effect of physician champions on the two main components of Kangaroo mother care (KMC): skin-to-skin care and breastfeeding. Methods KMC practices among a retrospective cohort of 648 infants admitted to a rural Indian neonatal intensive care unit (NICU) between 5 January 2011 and 7 October 2014 were studied. KMC champions were identified based on their performance evaluation. We examined the effect of withdrawing physician champions on overall use, time to initiation and intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 28 publications
(29 reference statements)
0
33
0
1
Order By: Relevance
“…At health systems level [ 23 , 24 ], identified barriers include absence of leadership (leading to infrastructure shortages, lack of space and poor privacy in hospitals), lack of provision of transportation services to health facilities, inflexible visitation policies for parents, insufficient staff and leaders in the field, and an absence of KMC champions (e.g. in rural western India [ 25 ]). Perverse financial mechanisms that rewarded traditional incubator/warmer care instead of promoting prolonged skin-to-skin contact were also discussed.…”
Section: Barriers To and Enablers Of Kangaroo Mother Carementioning
confidence: 99%
“…At health systems level [ 23 , 24 ], identified barriers include absence of leadership (leading to infrastructure shortages, lack of space and poor privacy in hospitals), lack of provision of transportation services to health facilities, inflexible visitation policies for parents, insufficient staff and leaders in the field, and an absence of KMC champions (e.g. in rural western India [ 25 ]). Perverse financial mechanisms that rewarded traditional incubator/warmer care instead of promoting prolonged skin-to-skin contact were also discussed.…”
Section: Barriers To and Enablers Of Kangaroo Mother Carementioning
confidence: 99%
“…Facilitators are crucial in translating the evidence into clinical practice, as shown by Soni et al. in this issue of Acta Paediatrica . They showed that two doctors were the key facilitators in promoting skin‐to‐skin contact in neonates admitted to an Indian neonatal intensive care unit.…”
mentioning
confidence: 97%
“…Thereafter, the risk of regressing back to old practices becomes smaller, even if some individuals moved away. According to the study reported in this issue , breastfeeding remained at the same level even after the champion doctors had moved to other units. However, some of the elements required for sustainability in the everyday practice of skin‐to‐skin contact had not been reached, as there was a significant decrease in the skin‐to‐skin practice after the champions had moved away.…”
mentioning
confidence: 98%
See 2 more Smart Citations